USING STRUCTURE FROM MOTION (SFM) TECHNIQUE FOR THE CHARACTERISATION OF RIVERINE SYSTEMS - CASE STUDY IN THE HEADWATERS OF THE VOLGA RIVER - P. Thumser; V. V. Kuzovlev; K. Y. Zhenikov; Yu. N. Zhenikov; M. Boschi; P. Boschi; M. Schletterer (Geography, Environment, Sustainability)
Digital terrain models (DTM) were produced with the structure from motion (SfM) technique, using data from high resolution terrestrial photography. In addition 360-degree spheres were created from ground taken photos. These spheres allow capturing the environment at this moment and coming back to the environment virtually later on. Also overlapping this virtual realty of the environment with model results can be used for distributing study results to a broad audience. On this basis hydraulic and morphological conditions were assessed and compared to field records. The proposed methods enable the creation of a detailed view on different riverine systems, i.e. from small to large rivers. This enables a morphodynamic characterisation which can be linked with the biological dataset of the monitoring project REFCOND_VOLGA. We propose that environmental intelligence gathering using ground-based as well as remote sensing observations can be applied increase the scope of scientific surveillance, and can lead to new opportunities to detect and quantify complex ecological interactions across a wide spectrum of scales.